Analisis Sistem Pengkondisian Udara Pada Ruang Kerja Kantor PT. Sarku Enjinering Utama - -, Matsuani; -, Suwaryo (Rekayasa Material, Manufaktur dan Energi, 2020)
Air conditioning in the workspace is something that workers need to provide comfort. Generally a comfortable condition (comfort condition) is an air condition where the temperature of the dry bulb is 24 C to 25 C and wet bulb is 18.3 C with relative humidity of 50% to 60%. The purpose of this study is to analyze the cooling requirements in the workspace which are then adjusted to the heat load in the room. In the calculation of the cooling load using the CLTD (Colling Load Temperature Difference) method. The final result is that the maximum cooling load at peak conditions is at 15:00 amounting to 14,152 kW = 182,941.99 BTU / h with an air requirement of 5,756 CFM, while the installed cooling capacity is 180,000 BTU / h resulting in a shortage of cooling load of 2,941, 99 BTU / h. With these deficiencies, additional air conditioning is needed as much as 2 units with each unit with a capacity of 1 PK / 9,000 BTU / h. Researchers recommend a cooling machine that is used to add capacity shortages, namely using a Split type AC cooler because it is considered more efficient and easy to install and maintain.